Dynamic Econometric Modeling and Policy Analysis of the Libyan Wheat Market - Elbeydi, Khaled R.M. (2005)
Wheat plays a major role in food contribution, it is considered as a principal food grain in the daily life of the people in Libya. In addition, wheat is an important commodity to the Libyan economy in terms of its contribution to the country’s GDP, food requirement and farm income.